2017
DOI: 10.1074/jbc.m116.757864
|View full text |Cite
|
Sign up to set email alerts
|

A Late G1 Lipid Checkpoint That Is Dysregulated in Clear Cell Renal Carcinoma Cells

Abstract: Lipids are important nutrients that proliferating cells require to maintain energy homeostasis as well as to build plasma membranes for newly synthesized cells. Previously, we identified nutrient-sensing checkpoints that exist in the latter part of the G phase of the cell cycle that are dependent upon essential amino acids, Gln, and finally, a checkpoint mediated by mammalian target of rapamycin (mTOR), which integrates signals from both nutrients and growth factors. In this study, we have identified and tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…These data suggest that cell cycle progression and lipid homeostasis are coordinated by a shared mechanism acting at the G 1 /S transition, thus implying that lipid droplet maintenance, biogenesis, or consumption is involved in cell cycle progression through S phase. In fact, a lipid-dependent metabolic checkpoint was recently described in late G 1 phase (51). Moreover, the fast lipid droplet dispersion within S phase identified in our study through BrdU staining is correlated with different stages of DNA synthesis, suggesting that molecules involved in the G 1 /S transition or S-phase progression could be acting in this process.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that cell cycle progression and lipid homeostasis are coordinated by a shared mechanism acting at the G 1 /S transition, thus implying that lipid droplet maintenance, biogenesis, or consumption is involved in cell cycle progression through S phase. In fact, a lipid-dependent metabolic checkpoint was recently described in late G 1 phase (51). Moreover, the fast lipid droplet dispersion within S phase identified in our study through BrdU staining is correlated with different stages of DNA synthesis, suggesting that molecules involved in the G 1 /S transition or S-phase progression could be acting in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, prior studies have suggested that proteins that promote lipolysis, such as ATGL and CGI‐58, may act as tumor suppressor proteins through unknown mechanisms . Recent studies have also begun to elucidate distinct lipid‐mediated cell cycle checkpoints in other systems, and thus new interactions between lipid metabolism and cell proliferation are likely to be clarified by ongoing work.…”
Section: Discussionmentioning
confidence: 99%
“…Commitment could be achieved with as little a 1 h treatment with plateletderived growth factor, whereas progression was more complicated involving IGF1 and other undetermined factor(s) in serum [11,12]. We recently identified a late G 1 cell cycle checkpoint that monitored the presence of fatty acids (FAs) [5]. We therefore wanted to determine whether lipids in serum contribute to late G 1 cell cycle progression into S-phase.…”
Section: Bsa Stimulates the Progression Of Fetal Bovine Serum (Fbs)-primed Bj-htert Human Fibroblasts From G 0 Into S-phasementioning
confidence: 99%
“…There are several metabolic checkpoints in late G 1 that check for both nutrient sufficiency and genomic integrity [1,2]. The metabolic checkpoints monitor the presence of essential amino acids, glutamine, and lipids [5,6]. There is also a checkpoint mediated by mammalian target of rapamycin complex 1 (mTORC1) [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation